Analisis Kepastian Hukum Dalam Penerapan Hukum Perikatan Pada Transaksi E-Commerce di Indonesia - Randi Adi Saputra; Wahyudi Wahyudi; Nana Suryana; Siti Putri Indah Meilani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The development of information technology has driven the rapid growth of e-commerce transactions in Indonesia, thus demanding adequate legal certainty in legal relations between parties. This study analyzes the application of contract law in e-commerce transactions with a focus on the legal certainty provided by laws and regulations, specifically the Civil Code (KUHPerdata), the Electronic Information and Transactions Law (UU-ITE), and their derivative regulations. The research method used is a normative juridical approach through an analysis of positive legal norms governing electronic agreements, the validity of contracts, and the responsibilities of the parties in digital transactions. The results of the analysis indicate that in principle, contracts arising from electronic agreements have the same legal force as conventional agreements as long as they meet the requirements for valid agreements as stipulated in the Civil Code. However, obstacles remain in practice, such as weak consumer and business understanding of electronic evidence mechanisms, suboptimal law enforcement against digital defaults, and limited supervision of marketplace platforms. This study concludes that legal certainty in e-commerce transactions can be achieved if regulations regarding electronic contracts are continuously strengthened, accompanied by increased digital legal literacy and more effective government oversight. These findings are expected to contribute to the development of a legal framework that is more adaptive to the dynamics of the digital economy in Indonesia.